MENINGKATKAN BERPIKIR KRITIS DAN KERJASAMA SISWA MENGGUNAKAN MODEL SERIUS DI KELAS V SDN SUNGAI ANDAI 3 BANJARMASIN - Mahfuzah, Rezka; Noorhapizah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was carried out to address the lack of critical thinking and collaboration among students in mathematics learning. The problems identified were linked to students’ difficulty in grasping mathematical concepts, insufficient exposure to practice questions, and low individual engagement in group responsibilities. To respond to these challenges, the SERIUS learning model was adopted as a strategic intervention. The study aimed to cultivate critical thinking and reinforce teamwork during learning activities among fifth-grade students at SDN Sungai Andai 3. During the second semester of the 2024/2025 school year, the research process followed the Classroom Action Research (CAR) model to systematically address the issues identified in the classroom approach methodology with a total of 36 participants 21 boys and 15 girls. Data were gathered through observations for qualitative analysis and written assessments, both individual and collaborative, for quantitative analysis. The results showed notable progress, with students' critical thinking improving from 47% in the initial session to 89% in the final meeting. Similarly, collaborative abilities rose from 44% to 89% over the same period. These outcomes indicate that the SERIUS model can serve as an effective alternative in mathematics instruction to strengthen both cognitive and interpersonal student skills.